(untitled) (World Bulletin of Social Sciences, 2024)
This article provides information on terminology issues in the Uzbek language and the study of field-related terms in it. Linguistic analysis of the terminological system of the field of “interior design” is also carried out. During the analysis, scientific and theoretical opinions are given about the influence of loanwords in terminology, especially the role of anglicisms in Uzbek terminology. In the analysis of the article, many Uzbek and English dictionaries related to the field of “interior design” were selected as sources.